Decomposing the Inflation Dynamics in the Philippines - Guo, Si (IMF Working Papers; Working Paper ;, 2019)
Inflation rates rose sharply in the Philippines during 2018. Understanding the demand and supply sources of inflation pressures is key to monetary policy response. Qualitatively, indicators have pointed to evidence of inflation pressures from both sides in 2018, with the supply factors, by and large, associated with commodity-price shocks and demand factors deduced from gleaning at the wider non-oil trade deficits seen in the Philippines. Quantitatively, we deploy a semi-structural model to decompose the contributions of various shocks to inflation. Our main findings are (1) supply factors (mainly global commodity prices) played a prominent role in explaining the rise in inflation in 2018; (2) demand factors also contributed to inflation in a non-negligible way, justifying the need for tighter monetary policy in 2018; (3) the size of the estimated output gap (an important indicator of demand pressures) could be larger, when considering the widening trade deficits in 2018; and (4) a delayed monetary policy tightening can be costly in terms of higher inflation rates, requiring larger and more aggressive interest rate hikes to bring inflation under control, based on a counterfactual exercise.